2023
DOI: 10.3390/cancers15143647
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Estrogen for the Treatment of Endocrine-Resistant Breast Cancer: Novel Therapeutic Approaches

Nivida Shete,
Jordan Calabrese,
Debra A. Tonetti

Abstract: Estrogen receptor (ER)-positive breast cancer is the most common subtype, representing 70–75% of all breast cancers. Several ER-targeted drugs commonly used include the selective estrogen receptor modulator (SERM), tamoxifen (TAM), aromatase inhibitors (AIs) and selective estrogen receptor degraders (SERDs). Through different mechanisms of action, all three drug classes reduce estrogen receptor signaling. Inevitably, resistance occurs, resulting in disease progression. The counterintuitive action of estrogen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…The two questions regarding the estrogen paradox were investigated in a series of elegant in vitro experiments by Dr. V.C. Jordan and others in his laboratory who have used ER+ breast cancer cell lines conditioned by long-term estrogen depletion to simulate the five-year post-menopausal gap (reviewed in [ 6 ]). They showed that the response to estrogen alternates between growth induction and suppression.…”
Section: Estrogen-induced Regression In Er+ Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…The two questions regarding the estrogen paradox were investigated in a series of elegant in vitro experiments by Dr. V.C. Jordan and others in his laboratory who have used ER+ breast cancer cell lines conditioned by long-term estrogen depletion to simulate the five-year post-menopausal gap (reviewed in [ 6 ]). They showed that the response to estrogen alternates between growth induction and suppression.…”
Section: Estrogen-induced Regression In Er+ Cancersmentioning
confidence: 99%
“…This cycling of the response to estrogen between growth induction and suppression mediated by intermittent estrogen exposure and the resulting change in the level of ER has led to the suggestion that “pre-emptively switching between estrogen and estrogen deprivation therapies before resistant tumors emerge is an effective strategy for long-term control of tumor burden” [ 7 ]. This laboratory advancement is driving the development of therapeutics that can condition or assist in estrogen-induced apoptosis [ 6 ] and has served as the basis for at least one large clinical trial, The Study Of Letrozole Extension (SOLE), a phase III randomized clinical trial of continuous vs. intermittent letrozole in post-menopausal women.…”
Section: Estrogen-induced Regression In Er+ Cancersmentioning
confidence: 99%
See 1 more Smart Citation